2006
DOI: 10.1248/bpb.29.1366
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Agaricus blazei on Mast Cell-Mediated Anaphylaxis-Like Reactions

Abstract: Agaricus blazei is a medically important mushroom widely eaten and prescribed around the world. It is belonged to the Agaricaceae family and is popularly known as "Himematsutake" in Japan. In Brazil, this mushroom is used as a traditional medicine for the prevention of cancer, diabetes, hyperlipidemia, arteriosclerosis, and chronic hepatitis. Recently, it has been reported that Agaricus blazei has the anti-tumor, immunomodulatory, anti-mutagenic, anti-oxidant, and anti-bacterial activities.1-6) However, it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Our report agrees with AbM-induced anti-inflammatory and antiallergic effects found in mouse bone marrow-derived mast cells [71], the inhibitory effect on mast cell-mediated anaphylaxis-like reactions in mice [72], and the amelioration of skewed Th1/Th2 balance in asthmatic [66] and allergic mice [52]. On the other hand, it disagrees with reports on proatherogenic and proinflammatory effects of AbM in a mouse model for atherosclerosis [73] and a clinical randomized trial that found no immunomodulatory effect in elderly women who received dried AbM extract [74].…”
Section: Discussionsupporting
confidence: 92%
“…Our report agrees with AbM-induced anti-inflammatory and antiallergic effects found in mouse bone marrow-derived mast cells [71], the inhibitory effect on mast cell-mediated anaphylaxis-like reactions in mice [72], and the amelioration of skewed Th1/Th2 balance in asthmatic [66] and allergic mice [52]. On the other hand, it disagrees with reports on proatherogenic and proinflammatory effects of AbM in a mouse model for atherosclerosis [73] and a clinical randomized trial that found no immunomodulatory effect in elderly women who received dried AbM extract [74].…”
Section: Discussionsupporting
confidence: 92%
“…45 Ca uptake. The calcium uptake of mast cells was measured according to the method described by Choi et al (2006). Purified mast cells were resuspended in HEPES-Tyrode buffer containing 45 Ca (1.5 mCi/mL; 1 Ci = 3.7 ¥ 10 10 becquerels; Perkin-Elmer Life Sciences, MA, USA) and incubated at 4°C for 10 min.…”
Section: Introductionmentioning
confidence: 99%
“…Mice (n=5/group) received an intraperitoneal injection of compound 48/80 (1, 4 and 8 mg/kg, i.p ) as described previously [15][16]. Curcumin (5, 10 and 20 mg/kg, i.p ) was administered an hour prior to administration of compound 48/80.…”
Section: Methods ---Compound 48/80-induced Systemic Anaphylactic Reacmentioning
confidence: 99%
“…In addition, previous studies demonstrated that curcumin had an inhibitory effect on histamine release from mast cells triggered by IgE, calcium ionophore A 23187, or concanavalin A [13][14][15]. Studies have suggested that curcumin has downregulated Th2 response and reduced lung inflammations in latex sensitized mice suggesting possible role of curcumin in controlling allergic disorders [16]. Studies demonstrate that known mast cell stabilizer, DSCG has mast cell stabilizing activity after nonimmunological stimulations [17].…”
Section: Introductionmentioning
confidence: 99%